Build an internet for, and from, us all. (29th November 2018) - Sengupta, Anasuya; Bouterse, Siko; Allmann, Kira
If the digital revolution is to democratize knowledge, it must include the voices of marginalized communities, say Anasuya Sengupta, Siko Bouterse and Kira Allmann. If the digital revolution is to democratize knowledge, it must include the voices of marginalized communities, say Anasuya Sengupta, Siko Bouterse and Kira Allmann.